The Economics of Predation: What Drives Pricing When There Is Learning-by-Doing? - Besanko, David; Doraszelski, Ulrich; Kryukov, Yaroslav (American Economic Review, 2014)
We formally characterize predatory pricing in a modern industry-dynamics framework that endogenizes competitive advantage and industry structure. As an illustrative example we focus on learning-by-doing. To disentangle predatory pricing from mere competition for efficiency on a learning curve we decompose the equilibrium pricing condition. We show that forcing firms to ignore the predatory incentives in setting their prices can have a large impact and that this impact stems from eliminating equilibria with predation-like behavior. Along with the predation-like behavior, however, a fair amount of competition for the market is eliminated. (JEL D21, D43, D83, K21, L13, L41)